PsycEXTRA Dataset 2014
DOI: 10.1037/e528942014-356
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Constraints in Motor Imagery

Abstract: Executed bimanual movements are prepared slower when moving to symbolically different than when moving to symbolically same targets and when targets are mapped to target locations in a left/right fashion than when they are mapped in an inner/outer fashion [Weigelt et al. (Psychol Res 71:238-447, 2007)]. We investigated whether these cognitive bimanual coordination constraints are observable in motor imagery. Participants performed fast bimanual reaching movements from start to target buttons. Symbolic target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 37 publications
3
13
1
Order By: Relevance
“…Most importantly, for proximal action elements visual and kinesthetic representations in the IMA group did not significantly differ from the representations in the execution groups. This is different from a previous observation, which indicated weaker kinesthetic representations in imagined than in executed reaching (Dahm & Rieger, 2016). It might be that visual feedback from the hands is more important in reaching than in darts.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Most importantly, for proximal action elements visual and kinesthetic representations in the IMA group did not significantly differ from the representations in the execution groups. This is different from a previous observation, which indicated weaker kinesthetic representations in imagined than in executed reaching (Dahm & Rieger, 2016). It might be that visual feedback from the hands is more important in reaching than in darts.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, we asked participants to report how strongly they represented/how much attention they paid to different aspects of the dart throws in IMA and EXE. Because it has previously been shown that some task-related representations are weaker in MI than in ME (Dahm & Rieger, 2016; Rieger & Massen, 2014), we expected weaker representations in MI than in ME. We further expected a larger difference between MI and ME in novices than in experts, because representations of dart throws may be less precise in novices than in experts (Rieger, 2012; Schack, 2004).…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…In the correlation analysis, positive associations of a moderate to strong magnitude were obtained between the time taken to generate motor images and the time taken for the execution of the real movement; previous studies found results similar to ours . It should be noted that the strongest correlations appeared between the execution of the movement and the generation of kinesthetic images in the three groups.…”
Section: Discussionsupporting
confidence: 82%